2019
DOI: 10.1038/s41598-019-49530-1
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Plasmodium falciparum and thrombin in brain endothelial barrier disruption

Abstract: Recent concepts suggest that both Plasmodium falciparum factors and coagulation contribute to endothelial activation and dysfunction in pediatric cerebral malaria (CM) pathology. However, there is still limited understanding of how these complex inflammatory stimuli are integrated by brain endothelial cells. In this study, we examined how mature-stage P. falciparum infected erythrocytes (IE) interact with tumor necrosis factor α (TNFα) and thrombin in the activation and permeability of primary human brain micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 77 publications
9
35
2
Order By: Relevance
“…Behaviour A was as expected and confirms that aPC rescues thrombin induced barrier disruption in HBMEC as seen above in EAhy926 cells. Behaviour B has been reported previously by several investigators using a range of co-culture systems ( Tripathi et al , 2007 ) ( Gillrie et al , 2012 ) ( Avril et al ., 2019 ), with either IE or parasite material affecting barrier integrity. The delayed recovery after thrombin addition was also reported by Avril et al .…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Behaviour A was as expected and confirms that aPC rescues thrombin induced barrier disruption in HBMEC as seen above in EAhy926 cells. Behaviour B has been reported previously by several investigators using a range of co-culture systems ( Tripathi et al , 2007 ) ( Gillrie et al , 2012 ) ( Avril et al ., 2019 ), with either IE or parasite material affecting barrier integrity. The delayed recovery after thrombin addition was also reported by Avril et al .…”
Section: Resultsmentioning
confidence: 62%
“…The delayed recovery after thrombin addition was also reported by Avril et al . when using schizont-stage IE in their TEER experiments ( Avril et al ., 2019 ). Based on these findings we have tested the compounds for their ability to block both behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in vivo trials in a controlled experiment showed a 17.7% increase in the endogenous thrombin generation in humans infected with P. falciparum, presenting a procoagulant state in the early stages of infection and indicating that the coagulation system reacts to infection and may play a role in the parasite lifecycle (Riedl et al 2016). Another study revealed the interaction between iRBC and thrombin in brain microvascular endothelial cell disruption, showing that erythrocytes infected with late-stage parasites induce endothelial cell death and increase permeability due to the action of thrombin and delayed tissue recovery (Avril et al 2019). Therefore, it is possible that iRBCs use the host's coagulation cascade to mediate cytoadhesion processes to the vascular endothelium to prevent spleen cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…Two mechanisms for the action of cytoadherence on coagulation/ inflammation dysregulation have been proposed (Figure 1). The direct binding of the P. falciparum variant surface protein P. falciparum erythrocyte membrane protein 1 (PfEMP1) to EPCR blocks the conversion of PC to aPC, affecting the ability of this host control system to control PAR1 cleavage by thrombin and altering the PAR1 signalling pathway (Avril et al, 2019;Gillrie et al, 2015;Kessler et al, 2017;Mosnier & Lavstsen, 2016;Sampath et al, 2015). This mechanism is dependent on the presence of EPCR-binding parasite variants, and these PfEMP1 types are strongly associated with severe malaria (Mkumbaye et al, 2017;Storm et al, 2019).…”
Section: Introductionmentioning
confidence: 99%